Analisis Dan Desain E-Comerce Pada Hasil Produk Pengolahan Ikan Asin - Arridha Zikra Syah; Fauriatun Helmiah (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
In industrial warehouse production that produces salted fish or or dried fish in the Gudang rejeki Keramat in Tanjung Balai can produce salted fish. As much as two tons a day and under certain conditions there is often fish production that accumulates in the warehouse because the processing is still using traditional methods. This method is related to food storage resilience that must be done is by accelerating the distribution of salted fish to customers, namely by utilizing information technology in marketing such as e-commerce, convenience is often an attraction such as easy access to choice of goods, ease of purchasing. Ease of payment to ease of getting goods or delivery of goods. The internet that allows store access from anywhere is one simple example of the convenience that e-commerce providers offer. Prospective buyer can now access the store from anywhere and when consumers find it easy to purchase product online, then security is compromised when making payments, including shipping goods that arrive properly, then convenience can be created. Convenience will bring customer satisfied, of course they will come back to buy online.